Preventive effects of ulinastatin on complications related to pancreaticoduodenectomy: A Consort-prospective, randomized, double-blind, placebo-controlled trial. Issue 24 (June 2016) - Zhang, Hao; Tan, Chunlu; Wang, Xing; Kang, Deying; Chen, Yonghua; Xiong, Junjie; Tian, Bole; Li, Kezhou; Hu, Weiming; Chen, Xiaoli; Ke, Nengwen; Li, Ang; et al.
Abstract : Abstract: Postoperative pancreatic fistula (POPF) is one of the most common major complications after pancreaticoduodenectomy (PD). Ulinastatin is an intrinsic trypsin inhibitor and mainly used to treat acute pancreatitis, chronic recurrent pancreatitis, and acute circulatory failure. The study aims to investigate the efficacy of ulinastatin on pancreatic fistula and other complications after PD. This prospective, randomized, double-blind, placebo-controlled trial was conducted in West China Hospital of Sichuan University from December 2012 to December 2014. A total of 106 consecutive patients undergoing PD were randomly assigned to receive ulinastatin or placebo during and after the surgery for 5 days. Baseline clinical characteristics and outcomes of patients were recorded and analyzed. Ninety-two patients including 42 in the ulinastatin group and 50 in the placebo group were available for outcome assessment. The POPF rates were comparable between ulinastatin group (43%) and placebo group (26%), whereas the severe pancreatic fistula rate (grade B + C) was significantly less in ulinastatin group than that in placebo group (7% vs 24%, P = 0.045). For patients with small pancreatic duct diameter (⩽3 mm), ulinastatin could significantly reduce the risk of POPF ( P = 0.022). Ulinastatin had protective effects for patients undergoing PD on the prevention of severe postoperative pancreatic fistula.